2022
DOI: 10.1038/s41398-022-02196-2
|View full text |Cite
|
Sign up to set email alerts
|

Neandertal introgression partitions the genetic landscape of neuropsychiatric disorders and associated behavioral phenotypes

Abstract: Despite advances in identifying the genetic basis of psychiatric and neurological disorders, fundamental questions about their evolutionary origins remain elusive. Here, introgressed variants from archaic humans such as Neandertals can serve as an intriguing research paradigm. We compared the number of associations for Neandertal variants to the number of associations of frequency-matched non-archaic variants with regard to human CNS disorders (neurological and psychiatric), nervous system drug prescriptions (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 65 publications
3
10
0
Order By: Relevance
“…Second, recent genetic modifications in the modern-day human genome reveal a particular enrichment for psychiatric traits (e.g. depression, alcohol intake; SI Appendix ), in line with recent evidence showing that introgressed variants from Neanderthals (variants relatively recent in human evolution) are linked to smoking, alcohol consumption, and mood-related traits (48); and with findings of an overrepresentation of alleles conferring risk for mood-related traits specifically in ancient farmers genome (∼11,000 years old) but not in evolutionary previous hunter-gatherer genome (49). Third, genes related to neuropsychiatric conditions (SCZ, BD, and AD) were found to contain more recent genetic modifications compared to other genes.…”
Section: Discussionsupporting
confidence: 67%
“…Second, recent genetic modifications in the modern-day human genome reveal a particular enrichment for psychiatric traits (e.g. depression, alcohol intake; SI Appendix ), in line with recent evidence showing that introgressed variants from Neanderthals (variants relatively recent in human evolution) are linked to smoking, alcohol consumption, and mood-related traits (48); and with findings of an overrepresentation of alleles conferring risk for mood-related traits specifically in ancient farmers genome (∼11,000 years old) but not in evolutionary previous hunter-gatherer genome (49). Third, genes related to neuropsychiatric conditions (SCZ, BD, and AD) were found to contain more recent genetic modifications compared to other genes.…”
Section: Discussionsupporting
confidence: 67%
“…This observation is consistent with recent studies using UK Biobank data that showed introgressed variants were depleted for contribution to the heritability of most complex traits or at least not enriched. 21,22 These studies did not specifically focus on neurodegenerative diseases. Our findings suggest that Neanderthal admixture is unlikely to have maintained the common genetic variant architecture of these neurodegenerative diseases in modern humans.…”
Section: Discussionmentioning
confidence: 99%
“…20 More recently, two studies aimed to address the complex nature of medically-relevant traits and the genome-wide influence of Neanderthal admixture using UK Biobank data. 21,22 The former study found that Neanderthal introgression did not significantly contribute to neurological and psychiatric traits and the latter found that introgressed variants were depleted for heritability of high-level cognitive traits. 22 However, neither looked specifically at neurodegenerative diseases of interest.…”
Section: Introductionmentioning
confidence: 99%
“…This observation is consistent with recent studies using UK Biobank data that showed introgressed variants were depleted for contribution to the heritability of most complex traits or at least not enriched. (Dannemann et al, 2022;McArthur et al, 2021) These studies did not specifically focus on neurodegenerative diseases. Our findings suggest that Neanderthal admixture is unlikely to have maintained the common genetic variant architecture of these neurodegenerative diseases in modern humans.…”
Section: Discussionmentioning
confidence: 99%
“…(Simonti et al, 2016) More recently, two studies aimed to address the complex nature of medically-relevant traits and the genomewide influence of Neanderthal admixture using UK Biobank data. (Dannemann et al, 2022;McArthur et al, 2021) The former study found that Neanderthal introgression did not significantly contribute to neurological and psychiatric traits and the latter found that introgressed variants were depleted for heritability of high-level cognitive traits. (McArthur et al, 2021) However, neither looked specifically at neurodegenerative diseases of interest.…”
Section: Introductionmentioning
confidence: 99%